Benefits of using the eye-tracking method for qualitative observation of students' multiplechoice physics tasks solution process - Martina Kekule; Iva Spanova; Jouni Viiri (Czech Pedagogical Society, 2020)
As previous studies have shown, the eye-tracking method is useful for monitoring cognitive processes. In this study, we focus on the benefits of analysing high school students' problem-solving processes when completing a multiple-choice test. Specifically, we provide a qualitative analysis of eye-movements of two low prior knowledge students as they solve two physics tasks. Both students scored zero on the test and chose the same options. In a paper-pencil administration of such a test, we would receive the same results from both of them. Via analysis of the eye-tracking data, we have shown that there are several similarities and differences between their solving approaches. Particularly, they both emphasized the key terms in the stem, meaning they did not provide incorrect answers due to improper stem reading. Both students showed very typical misconceptions concerning understanding Newton's First Law. However, they differ in their confidence. Eve arrived at her answer quicker, but Jane needed to reread the stem many times. We observed atypical saccadic eye movements when Eve read the stems of the tasks and much longer fixations when she suddenly switched to her answers. Jane showed "graph as a picture error" when interpreting an illustrative picture in the stem. Based on our analysis, we demonstrate that summarized data on areas of interest (AOIs) can be misleading when AOIs are too large (e.g., each test option). We also introduce several indicators appropriate for a qualitative analysis, and we present new visualisations for in-word and between-words saccades.